1972
DOI: 10.1002/macp.1972.021540102
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium ring‐opening polymerization of mono‐ and multicyclic unsaturated monomers

Abstract: Equilibrium ring-opening polymerization theory has been extended to cycloolefin polymerizations. Previous work had established the reversible nature of the olefin metathesis reaction, the basic process whereby cycloolefins undergo ring-opening. The present work confirms the reversible character of cycloolefin polymerization for the cases of cyclopentene and bicyclo[4.3.0]nona-3.7-diene polymerization. Equilibrium conversion data for cyclopentene polymerizations have provided estimates of the enthalpy (-4.4 kca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
1
1

Year Published

1980
1980
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(58 citation statements)
references
References 13 publications
4
52
1
1
Order By: Relevance
“…equilibrium concentration) was influenced only by the applied reaction temperature. 10 The thermodynamic parameters for the cyclopentene polymerization employing ruthenium-based complexes were calculated and found to be lower than those of achieved via tungsten catalyzed systems. Table 1).…”
Section: Resultsmentioning
confidence: 97%
“…equilibrium concentration) was influenced only by the applied reaction temperature. 10 The thermodynamic parameters for the cyclopentene polymerization employing ruthenium-based complexes were calculated and found to be lower than those of achieved via tungsten catalyzed systems. Table 1).…”
Section: Resultsmentioning
confidence: 97%
“…Whereby, the monomer conversion is dependent on the reaction temperature and not the catalyst activity, resulting in a monomer-polymer equilibrium. 54,55 PIB Ru complex 8 was prepared following previously published protocols. The catalytic activity of complexes HG2 and 8 were evaluated for the equilibrium ROMP of monomer M4 at two different temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…6 The thermodynamic study using WCl 6 /Al(C 2 H 5 )Cl 2 catalysts revealed that the cyclopentene conversion does not depend on the catalyst activity but the reaction temperature. 7 This observation indicated characteristic monomer-polymer equilibrium.…”
Section: Introductionmentioning
confidence: 86%